(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Agrio Formation (Valanginian to early Barremian) is a siliciclastic and carbonate unit of the Neuquén Basin in west central Argentina. A conspicuous 20 m thick dolomitized section near the top of the upper Agua de la Mula Member of the Agrio Formation was identified for the first time in this unit. The analyzed section is composed of dolostones with scarce siliciclastic intercalations. A tidal flat environment with highfrequency cycles is suggested for the measured section. Petrography, SEM, X-Ray, EDAX and cathodoluminiscence analyses showed two different dolomitization processes. The first one comprises early mimetic and non mimetic dolomitization on ooids, bioclasts and early marine cements. The second one reveals precipitation of dolomite cement. The mimic dolomitization indicates that this process took place before the inversion from aragonite to calcite, or from low magnesium calcite to high magnesium calcite. The dolomitization should have been soon after the deposition. The presence of dolomite cement is probably related to a high concentration of Mg2+ coming from sea water flushing into highly porous sediments mixed with fresh waters from the continent. This is suggestive of a change of diagenetic environment from marine to meteoric, probably during sea level changes. A model that explains these processes is the shallow seawater dolomitization model. This model proposes that dolomitization is triggered by the drive of large amount of seawaters through the sediments.